SARS-CoV-2 seroprevalence in French 9-year-old children and their parents after the first lockdown in 2020 - Charles, Marie Aline; Ancel, Pierre-Yves; Simeon, Thierry; Marchand-Martin, Laetitia; Zaros, Cécile; Dufourg, Marie-Noelle; Benhamou, Valérie; Blanché, Hélène; Deleuze, Jean-François; Rahib, Delphine; Lydie, Nathalie; de Lamballerie, Xavier; et al. (Frontiers in Pediatrics, 2023)
Children have been significantly less affected by COVID-19 than adults and presented with milder and less symptomatic forms of the disease. However, there has been suggestion that children older than 10 years and adolescents exhibits features closer to that of young adults.Most studies combine children in different age-groups and lack sufficient numbers to explore in detail age specificities. We report data on a population-based sample of 2555 children at the pivotal age of 9 years.In April 2020, the participants in two French nationwide cohorts of children, Elfe and Epipage2, were invited to take part into an online survey about Covid related symptoms and family life during the lockdown. A second questionnaire was sent on May 5. This questionnaire also proposed to the child included in the cohort and to one of his/her parents to take part into a capillary blood collection for Covid serology. Families who agreed to the serological survey were sent kits for dried blood spots self-sampling (DBS) with instructions. Samples were processed with a commercial Elisa test (Euroimmun®, Lübeck, Germany) to detect anti-SARS-CoV-2 antibodies (IgG) directed against the S1 domain of the spike protein of the virus.Children's acceptance rate for the serological survey was around 60%. 2555 serological results were analyzed. The weighted prevalence of a positive Elisa Spike serology was 2.8% in 9 yrold children (95% CI: 1.7%-4.0%). Positive serology was found in 8.6 % (7.4%-9.7%) of parents who provided blood. There was a significant association (p<0.001) between serology of the child and parent from the same household with an odds ratio of 13.8 (7.9-24.2)).In conclusion: we have shown that 9-yr old children had a lower susceptibility to SARS-Cov2 infection than adults with the initial Chinese strain, similar to younger children and estimated that around 3% of them have developed antibodies against SARS-Cov2 in France after the first wave of the Covid-19 epidemics.